Navigating capital value: A holistic study on profitability and capital structure influences: Inggris - Maisa Azizah Asmara; Maya Sari; Ervie Nur Afifa Mukhlis; Hamidah; Rivaldi Arissaputra (Jurnal Mantik, 2023)
Indonesia's energy sector has been affected by the economic downturn, where the energy sector that has been the mainstay throughout 2022 has also experienced a significant decline due to reduced demand resulting in lower commodity prices. This study is to investigate the effect of profitability as measured by ROA and capital structure with DER on firm value with PBV. The approach used was causal associative and the sample selected was 37 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022 period. The data analysis technique uses multiple liner regression analysis with SPSS 26 tools. The results showed that profitability and capital structure had no effect on firm value